Code-switching in EFL classrooms: factors influencing teachers to use code-switching and its types used in the classrooms - Sri Rejeki Murtiningsih; Munawaroh Munawaroh; Sibakhul Milad Malik Hidayatulloh (Journal on English as a Foreign Language, 2022)
Among myriad prior studies on code-switching, little has been done on the factors influencing teachers to use code-switching and their classroom practices. The current research was aimed at investigating the motives of EFL teachers applying code-switching and the sorts of code-switching used by the EFL teachers in the classroom. This study used a qualitative case study as a research design by conducting in-depth interviews and observations as a data collection process. The obtained data were analyzed through coding, i.e., finding the similarities of the data and theming. The research participants were two EFL teachers at a private university in Yogyakarta Indonesia who have code-switching experience when teaching. The research found five reasons teachers used code-switching in EFL teaching and learning: discussing specific topics, making teaching and learning more practical, managing the classroom, building social relationship, and encouraging students' active participation. In addition, the observation found three code-switching types used by EFL teachers in their classrooms. The study implies that while code-switching offers some benefits, teachers should use code-switching at a minimum rate to keep students with maximum exposure to the English language.